UMPs Ziarah Kasih visits SPM 11A high achieving student - Nor Salwana, Mohammad Idris (UMPSA, 2023)
BACHOK, 14 June 2023 - A delegation from Universiti Malaysia Pahang (UMP) visited and paid respects to Muhammad Syahril Saidi, an outstanding student from Sekolah Menengah Ugama (A) Darul Iman, Beris Lalang, Bachok, Kelantan.